Risk and Resilience in the Era of Climate Change - Thomas, Vinod. author. aut Link
XXXI, 201 p. 21 illus., 18 illus. in color.
Keywords: This book presents essential insights on the interaction between rising risks and raising the bar for resilience during the climate crisis. Its timeliness lies in applying important findings on risk and resilience to runaway climate change. When risk and resilience are brought together in the context of climate catastrophes, three key messages emerge. The first is that accounting for the root causes of these calamities, and not just their symptoms, is essential to slowing the spike in these events. It is therefore vital to link carbon emissions from human activity to the sharp rise in climate disasters globally. The second is that growth economics and policy must factor in the failure of governments and businesses to tackle spillover harm from economic activities, as seen dramatically with global warming. With climate risks rising, this calls for a fundamental revision in the teaching and practice of business and economics. And third, prevention must become a far bigger part of resilience building, with greater preparedness for more intense destruction built into interventions. This emphasis on prevention deems disaster recovery as not just returning to how things were but building back better. Vinod Thomas, Visiting Professor at Lee Kuan Yew School of Public Policy, National University of Singapore, was Senior Vice President, Independent Evaluation, at the World Bank, and Director General of Independent Evaluation at the Asian Development Bank. He has authored 17 books, including Climate Change and Natural Disasters (2017).